A educação dos sentidos nas escolas Maristas: o Guide des Écoles - Assis, Paula Maria de (2013)
The study object of this research is the investigation on Education of the Senses at Marist schools through particular pedagogic methods built up from senses mobilization and experimental practices, in the period between 1853 and 1860. The time stretch is justified by the period when the Guide des Écoles was in use at the Congregation s schools, which goes from 1853, date of the first edition resulting from the works of the Second General Chapter of the Marist Brothers Institute until 1961, when the Vatican II Council was called, bringing forth great changes in the Catholic Church organization, leading to changing the educational guidelines and causing the Guide to stop being used. The hypothesis is that the Marist Congregation coming from Europe brought modern pedagogic methods of their own, developed under the aegis of science, experience, the education of the senses, and the catholic morale as a way to keep its status quo, theoretically based upon Saint Thomas de Aquino s thought. The research understands that Marist schools, in the perspective of the catholic universe of education, identify themselves with the other Congregations once they have a common matrix, namely, the policies coming from Vatican (Rome) and which in spite of the specificities around their way of acting are similar as far as the Christian moral formation proposal goes, of a citizen committed to faith and active in the Church. The core question guiding the work is What methodological proposals back up the Education of the Senses at catholic schools? And, in this perspective, the study shall center the analysis of the manual developed for the Brothers formation the Guide des Écoles. This choice is owing to modernity in the presentation of its method and the context in which it was developed, this being the core research source. The theoretical references to the analysis of this research are Peter Gay, E.P.Thompson and Arno Mayer